Mechanism of parent-of-origin effects revealed by multi-omic data in euro-chinese hybrid pigs - Chenyu Li; Mei Ge; Keren Long; Ziyin Han; Mingzhou Li; Zhiyan Zhang; Lusheng Huang (Nature Communications)
Abstract Parent-of-origin effects refer to the phenomenon whereby the gene expression and corresponding phenotype are influenced by paternal or maternal origin, and uncovering the underlying regulatory mechanisms remains a challenging task. To address this, we designed three sets of trio families by crossing divergent pig breeds to generate sufficient heterozygous loci and collected back fat and longissimus dorsi for multi-omics sequencing. Parental phases of sequencing reads are efficiently determined by leveraging long-read sequencing technology. We generate a phased multi-omics resource in hybrid pigs, identifying 10,516 phase-specific gene expressions, 104,708 methylated regions, 132,602 histone modifications, 25,667 CTCF binding sites, and, based on in situ Hi-C, 7884 topologically associated domain boundaries and 8573 chromatin loops. Our results reveal that, although nearly 83% of gene expression differences between parental phases are regulated by DNA methylation, a subset is still influenced by other epigenetic modifications. This study not only highlights complex imprinting regulation models of H19-IGF2 and SGCE-PEG10 but also provides insight into the inheritance of advantageous traits in hybrid offspring.